2020
DOI: 10.3389/fncel.2020.00159
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Mutations Differentially Regulate Cell-to-Cell Transmission of α-Synuclein

Abstract: Recent studies suggest that the cell-to-cell spread of pathological α-synuclein (α-syn) plays important roles in the development of Parkinson's disease (PD). PD patients who carry α-syn gene mutations often have an earlier onset and more severe clinical symptoms and pathology than sporadic PD cases who carry the wild-type (WT) α-syn gene. However, the molecular mechanism by which α-syn gene mutations promote PD remains unclear. Here, we hypothesized that pathogenic mutations facilitate the intercellular transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 114 publications
0
16
0
Order By: Relevance
“…PD patients with α-syn mutations associated with the early onset disease have more severe pathological symptoms than sporadic PD patients expressing wild-type α-syn. A study demonstrated that specific mutations that affect the α-syn protein structure, such as A53T, H50Q, and G51D, can promote the propagation of synucleinopathy and induce neuroinflammation in the substantia nigra pars compacta region of rats (Guan et al, 2020).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…PD patients with α-syn mutations associated with the early onset disease have more severe pathological symptoms than sporadic PD patients expressing wild-type α-syn. A study demonstrated that specific mutations that affect the α-syn protein structure, such as A53T, H50Q, and G51D, can promote the propagation of synucleinopathy and induce neuroinflammation in the substantia nigra pars compacta region of rats (Guan et al, 2020).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…For example, it was shown that H50Q and A53T mutations significantly increased aSyn secretion. Furthermore, H50Q, G51D, and A53T pre-formed fibrils efficiently seeded in vivo and acutely induced neuroinflammation [ 156 ]. These data indicate that pathogenic mutations augment the prion-like spread of aSyn.…”
Section: Lewy Pathology: More Than Simply One Mechanism or Hypothementioning
confidence: 99%
“…Studies injecting rodent/patient brainderived material were excluded due to concerns that the injectate is not homogenous and the concentration of aSyn and other protein components cannot be known or compared across studies. Although a number of studies have been published analyzing the differences in pathogenicity of fibrils of different conformations [12][13][14][15][16][17][18], different aSyn mutations [19][20][21][22], different aSyn truncations [23][24][25], and different aSyn post-translational modifications [26], these were excluded from the summary tables as the objective of these experiments is to compare pathogenicity relative to wildtype aSyn PFFs and therefore the nuanced information requires a different venue.…”
Section: Guide To Reading and Interpreting The Tablesmentioning
confidence: 99%